2022
DOI: 10.1111/sjop.12863
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the peer status prototypes: A large‐scale latent profile analysis on high‐school students from four European countries

Abstract: Peer status – the regard other group members have of an individual – is fundamental for youth development. Different research traditions developed independent theoretical frameworks conceiving the dimensions underlying social status, and this led to identifying a variety of peer status prototypes. In this work, we explored whether a classification based on the four dimensions of popularity, aggression, dislike, and victimization could integrate the scattered peer status profiles found in the different traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…There are different prototypical behavioural traits between victim and bully groups. For example, it is found that bullies are often characterised as prestigious, dominant, aggressive, and masculine, whereas victims exhibit both anxiety and aggressive traits (Marinucci et al, 2023;Moura et al, 2011).…”
Section: Categorization and Group Identification In Bullyingmentioning
confidence: 99%
“…There are different prototypical behavioural traits between victim and bully groups. For example, it is found that bullies are often characterised as prestigious, dominant, aggressive, and masculine, whereas victims exhibit both anxiety and aggressive traits (Marinucci et al, 2023;Moura et al, 2011).…”
Section: Categorization and Group Identification In Bullyingmentioning
confidence: 99%